Removable prosthodontics at a glance - Field, James, 1979-; Storey, Claire (At a Glance (Dentistry) Ser., 2020)
"Removable Prosthodontics at a Glance provides a comprehensive and accessible guide to the practical elements of complete and partial denture provision. It serves as the perfect illustrated guide for learners, and a handy revision guide for subsequent undergraduate and postgraduate studies. Following the familiar, easy to use at a Glance format, each topic is presented as a double page spread with text accompanied by clear colour diagrams and clinical photographs to support conceptual understanding. Key concepts such as patient assessment, material handling, denture design, making impressions, and much more are explained and superbly illustrated enabling the reader to visualise the intended clinical endpoint. Removable Prosthodontics at a Glance is a valuable resource for students studying dentistry and clinical dental technology, and those preparing for further studies in Prosthodontics"--